2004
DOI: 10.3354/meps269277
|View full text |Cite
|
Sign up to set email alerts
|

Migratory environmental history of the grey mullet Mugil cephalus as revealed by otolith Sr:Ca ratios

Abstract: We used an electron probe microanalyzer (EPMA) to determine the migratory environmental history of the catadromous grey mullet Mugil cephalus from the Sr:Ca ratios in otoliths of 10 newly recruited juveniles collected from estuaries and 30 adults collected from estuaries, nearshore (coastal waters and bay) and offshore, in the adjacent waters off Taiwan. Mean (± SD) Sr:Ca ratios at the edges of adult otoliths increased significantly from 6.5 ± 0.9 × 10 -3 in estuaries and nearshore waters to 8.9 ± 1.4 × 10 -3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 41 publications
1
71
0
9
Order By: Relevance
“…M. cephalus and L. ramado are good osmoregulators, as they maintain a stable internal osmolality in a wide range of external salinity levels, including fresh water (Lasserre and Gallis, 1975;Nordlie and Lefler, 1975;Nordlie et al,, 1982;Thomas, 1984;Kulikova et al,, 1989 these two species, the cost of osmotic regulation is the lowest within the oligomesohaline range (Nordlie and Lefler, 1975;Cardona, 1994Cardona, , 2000 and therefore growth is expected to be highest within that range, although experimental evidence is available only for M. cephalus (Cardona, 2000). Thus, it is not surprising to find that these two species showed a strong preference for sites with a salinity level under 15, although adults may prefer more saline areas (Cardona, 2000;Chang et al, 2004). However, Chang et al, (2004) have revealed the existence of individual differences in the habitat preference of M. cephalus in Taiwan, as most specimens avoid freshwater sites throughout their life whereas others spend long periods there.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…M. cephalus and L. ramado are good osmoregulators, as they maintain a stable internal osmolality in a wide range of external salinity levels, including fresh water (Lasserre and Gallis, 1975;Nordlie and Lefler, 1975;Nordlie et al,, 1982;Thomas, 1984;Kulikova et al,, 1989 these two species, the cost of osmotic regulation is the lowest within the oligomesohaline range (Nordlie and Lefler, 1975;Cardona, 1994Cardona, , 2000 and therefore growth is expected to be highest within that range, although experimental evidence is available only for M. cephalus (Cardona, 2000). Thus, it is not surprising to find that these two species showed a strong preference for sites with a salinity level under 15, although adults may prefer more saline areas (Cardona, 2000;Chang et al, 2004). However, Chang et al, (2004) have revealed the existence of individual differences in the habitat preference of M. cephalus in Taiwan, as most specimens avoid freshwater sites throughout their life whereas others spend long periods there.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, it is not surprising to find that these two species showed a strong preference for sites with a salinity level under 15, although adults may prefer more saline areas (Cardona, 2000;Chang et al, 2004). However, Chang et al, (2004) have revealed the existence of individual differences in the habitat preference of M. cephalus in Taiwan, as most specimens avoid freshwater sites throughout their life whereas others spend long periods there. Such variability may also be true for L. ramado, which is a species found over a wide range of salinity levels (Lafaille et al, 2002;Almeida, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Chang et al (2004) found that habitat use changed with the age of mullet (Mugil cephalus), such that 26.7% and 10.5% of age 1 + and 2 + mullet respectively inhabited fresh water and that no fish 3 + or older inhabited fresh water. In contrast, the number of mullet that migrated offshore from freshwater and estuarine areas increased with age (Chang et al 2004).…”
Section: Sr:ca Ratiosmentioning
confidence: 99%
“…Stable Sr:Ca ratios lower than 3.5 mg g −1 are generally associated with freshwater habitats (Chang et al 2004, Tabouret et al 2010, Feutry et al 2011). This species is thought to be catadromous and to reproduce at sea or in estuary plumes (Hogan & Nicholson 1987, Lewis & Hogan 1987).…”
Section: Kuhlia Rupestrismentioning
confidence: 99%